REGULATION OF IMMUNE RESPONSE OF PATIENTS WITH PARTIALLY CONTROLLED vs CONTROLLED BRONCHIAL ASTHMA - E. Yu. Barabash; E. P. Kalinina; T. A. Gvozdenko; Yu. K. Denisenko; T. P. Novgorodtseva; M. V. Antonyuk; K. K. Khodosova (Медицинская иммунология)
A control group included seventeen conditionally healthy people (Group 1). Eighty-eight patients with proven bronchial asthma (BA) at the age of 22 to 48 were enrolled into the study. I.e., Group 2 included nine patients with well-controlled BA. Group 3 included persons with partially controlled BA (n=79). There were 8 people with easily treated BA in group 2, and 57 such cases in Group 3. The levels of interleukins (IL-4, IL-10, IL-17A), interferon-γ (IFNγ), and tumor-α necrosis factor (TNFα) were monitored by means of flow cytometry technique. The parameters of cellular immunity were registered by flow cytofluorimetry assays. Phagocytosis indicators were studied by means of D. Mayansky method, metabolic activity of neutrophils, by the B.Park method, as modified by E.Shmelev. Evaluation of cellular immunity did not reveal statistically significant differences for distinct CD subpopulations between healthy controls and BA patients. The patients with controlled and partially controlled BA exhibited some changes in cytokine concentrations, i.e., increased IL-4, IL-17А, IL-10 and TNFα levels; changes in phagocytosis and oxygen dependent bactericidal activities of neutrophils. We have revealed higher concentrations of IL-4, IL-17А in the less controlled BA (group 3) , as compared with group 2. TNFα induction remained at significantly higher level in both groups of BA patients, exceeding mean control values by 2.3 times. The degree of IL-10 production in group 2 with controlled BA was significantly higher than in group with partial disease control (group 3, p < 0.001), thus suggesting application of IL-10 levels as an index of active inflammation control. Patients with BA (groups 2, 3) exhibited a decrease of basal IFNγ, as compared to healthy people (p < 0.001). In group 3 (partial control), this parameter was 3-fold lower than in healthy persons. Evaluation of monocyte/phagocyte functions showed statistically significant differences between BA patients and healthy persons. Functional reserve of granulocyte activity and oxidative metabolism were decreased to a similar degree in the patients with well-controlled and partially resistant BA, thus showing their independence on the quality of disease control.